Effect of multiple micronutrient-fortified bouillon on micronutrient status among women and children in the Northern Region of Ghana: Protocol for the Condiment Micronutrient Innovation Trial (CoMIT), a community-based randomized controlled trial. - Reina Engle-Stone; K Ryan Wessells; Marjorie J Haskell; Sika M Kumordzie; Charles D Arnold; Jennie N Davis; Emily R Becher; Ahmed D Fuseini; Kania W Nyaaba; Xiuping Tan; Katherine P Adams; Georg Lietz; et al. (PLoS ONE)
Introduction Micronutrient deficiencies are prevalent in West Africa, particularly among women of reproductive age (WRA) and young children. Bouillon is a promising food fortification vehicle due to its widespread consumption. This study aims to evaluate the impact of multiple micronutrient-fortified bouillon cubes, compared to control bouillon cubes (fortified with iodine only), on micronutrient status and hemoglobin concentrations among lactating and non-lactating WRA and young children in northern Ghana. Methods This randomized, controlled doubly-masked trial will be conducted in the Kumbungu and Tolon districts in the Northern Region of Ghana, where prior data indicate multiple micronutrient deficiencies are common. Participants will be: 1) non-pregnant non-lactating WRA (15-49 y), 2) children 2-5 y, and 3) non-pregnant lactating women 4-18 months postpartum. Eligible participants will be randomly assigned to receive household rations of one of two types of bouillon cubes: 1) a multiple micronutrient-fortified bouillon cube containing vitamin A, folic acid, vitamin B12, iron, zinc, and iodine, or 2) a control cube containing iodine only. Each participant's household will receive a ration of bouillon cubes every 2 weeks, and households will be advised to prepare meals as usual, using the study-provided cubes. The trial duration will be 9 months for non-pregnant non-lactating WRA and children, and 3 months for lactating women. The primary outcomes will be changes in biomarkers of micronutrient status and hemoglobin among WRA and children and milk micronutrient concentrations among lactating women. Secondary outcomes will include change in prevalence of micronutrient deficiency and anemia; dietary intake of bouillon and micronutrients; inflammation, malaria, and morbidity symptoms; and child growth and development. Discussion Evidence from this study will inform discussions about bouillon fortification in Ghana and West Africa. Trial registration The trial was registered on ClinicalTrials.gov (NCT05178407) and the Pan-African Clinical Trial Registry (PACTR202206868437931). This manuscript reflects protocol version 4 (August 29, 2022).